Pembiusan Babi Model Laparoskopi untuk Manusia dengan Zoletyl, Ketamin dan Xylazin - -, Gunanti; Siswandi, Riki; Soehartono, Raden Harry; Ulum, Mokhamad Fakhrul; Sudisma, I Gusti Ngurah (Jurnal Veteriner; Vol 12 No 4 (2011), 2012)
In the last decade the use of pig as animal model for trining in laparoscopic surgery showed onincreased in Indonesia. The training for laparoscopy surgery involved cholecystectomy, ovariohysterctomy,hysterectomy, nefrectomy, spleenectomy, and cardiosurgery. The success of such training depends on themethod and the process as such as the proper used to handle the animal. The study was a retrospectivestudy over 2009-2010 laparoscopic training on 62 pigs. The objective of this study was to elucidate theprocedure of pig laparoscopic surgery, anesthesia methods, obstacle, and the solutions. Method ofanesthesia induction was performed by using combination of tiletamine-zolazepam (8 mg/kg bw), ketamineHCl (6 mg/kg bw), and xylazine HCl (2 mg/kg bw) /ZKX without premedication. Anesthetized pigs weremaintained with combination of ketamine HCl (5 mg/kg bw)-xylazine HCl (2 mg/kg bw) without anyanalgesic agent. Onset of ZKX induction induction was 3-5 minutes. Time of surgery varied from 40 to 120minutes, depend on surgery procedures. Heart beat and respiration rate per minute were remain stableduring surgery procedure, with observed at 68.4±12.1 and 41.3±14.1 respectively. The anesthetic methodused for Indonesian local pigs appeared to be suitable for laparoscopic surgery model for human.
Keywords: pig anesthesia, ketamine, laparoscopic surgery, tiletamine-zolazepam